The potential of eliminating the grain sink for enhancing biofuel traits in sweet sorghum hybrids - Jebril, Jebril Ali Abdalla Mohamad (Kansas State University, 2018)
Sweet Sorghum [Sorghum bicolor (L.) Moench] is a type of cultivated sorghum grown primarily for its sugar-rich stalks. Because of its high fermentable sugar content, the crop is widely recognized as an alternative feedstock source for bio-fuel production. The extent to which stalk sugar accumulation occurs may be determined by several factors including the sink size. Grain is the most important sink in sorghum and other grain crops. Three experiments were conducted in this study to determine the extent to which the grain sink can reduce sugar accumulation in the stalks, to test and validate a genetic system that allows development of sterile sweet sorghum hybrids, and to assess the potential of sugar-rich hybrids to overcome stalk rot diseases. The first experiment, based on 22 sweet sorghum genotypes, was undertaken to study the effect of eliminating the grain sink (removing the head prior to anthesis) on stalk juice yield, sugar accumulation, and biomass. The data showed that the grain sink had a significant effect on all traits measured. Elimination of the grain sink significantly increased oBrix % (17.8%), dry biomass (27.8%), juice yield (23.9%), and total sugar yield (43.5%). The second experiment was aimed at validating the role of A3 genetic male sterility system for producing sterile sweet sorghum hybrids. Ten sweet sorghum pollinator lines of variable sugar content were selected among the entries included in the previous experiment. The lines were crossed to four A1 and A3 cytoplasmic male sterile (CMS) lines using a Design II mating scheme. The A3 females did not have effective restorers so that the hybrids were expected to be sterile. The parental lines and corresponding hybrids were evaluated for biomass production, oBrix, juice and sugar yield using a randomized complete block design. All A3 hybrids were sterile and did not produce seed when heads were covered prior to pollination. The effect of grain sink represented by the A1 vs. A3 CMS were highly significant for Brix%, biomass, juice, and sugar yield. Comparison of parents vs. crosses component was highly significant, indicating marked heterosis effect for the traits. Both general (GCA) and specific (SCA) combining ability effects were also significant for all traits, indicating the role of both additive and dominance genetic effects in the inheritance of the characters. Earlier studies have shown positive relationships between stalk sugar concentration and stalk rot disease resistance in sorghum. Thus, the objective of the third experiment was to study the effects of the CMS mediated differential accumulation of stalk sugar on severity of charcoal rot disease caused by Macrophomina phaseolina. The experiment provided an opportunity to test the effect of variable stalk sugar in the same genetic backgrounds. The data indicated that hybrids produced from A3 cytoplasm were more resistant to charcoal rot (7.1cm lesion length) compared to those produced from the A1 hybrids (9.5 cm lesion length). The enhanced resistance of hybrids with higher sugar yield could have significant agronomic advantage in sugar based bio-fuel feedstock production.
Keywords: Sorghum bicolor; Grain sink; Biomass yield; Juice yield; Cytoplasmic male sterility; Combining ability; Macrophomina phaseolina